Management of Vocational Souvenir Education to Develop Entrepreneurial Skills of Students with Disabilities: A Case Study at SMALB Bani Muttaqin and SMALB At-Turmudzi - Feny Afifah Purnamasari; Iim Wasliman (Journal of Science and Education (JSE), 2025)
This study explores the management of vocational souvenir education as a strategy to develop entrepreneurial skills among students with disabilities at SMALB Bani Muttaqin and SMALB At-Turmudzi. The research aims to analyze how the four management functions planning, organizing, actuating, and controlling (POAC) are implemented to support effective vocational learning and empowerment. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observations, and document analysis. The data were analyzed using Miles, Huberman, and Saldaña’s interactive model, while validity was ensured through triangulation of sources, methods, and time. The findings reveal that both schools have successfully integrated management principles with inclusive pedagogical practices. The planning process emphasizes creativity, adaptability, and resource optimization; organizing involves collaborative roles among principals, teachers, parents, and students; actuating focuses on experiential, hands-on learning that promotes creativity and confidence; and controlling adopts reflective supervision emphasizing formative evaluation and continuous improvement. Despite resource limitations, both schools demonstrated effective, human-centered management that nurtures self-reliance and entrepreneurial awareness among students. This study concludes that vocational souvenir education, when managed through an inclusive and adaptive approach, can transform vocational training into a meaningful process of entrepreneurial and social empowerment for students with disabilities. The research contributes theoretically by contextualizing Terry’s POAC framework in special education and practically by offering a replicable model for community-based vocational management. Strengthening strategic planning, partnerships, and evaluation systems is recommended to ensure program sustainability and broader impact